Formation of low-T hydrated silicates in modern microbialites from Mexico and implications for microbial fossilization - Zeyen, Nina; Benzerara, Karim; Li, Jinhua; Groleau, Alexis; Balan, Etienne; Robert, Jean-Louis; Estève, Imène; Tavera, Rosaluz; Moreira, David; López-García, Purificación (Frontiers in Earth Science, 2015)
Microbialites are organo-sedimentary rocks found in abundance throughout the geological record back to 3.5 Ga. Interpretations of the biological and environmental conditions under which they formed rely on comparisons with modern microbialites. Therefore, a better characterization of diverse modern microbialites is crucial to improve such interpretations. Here, we studied modern microbialites from three Mexican alkaline crater lakes: Quechulac, La Preciosa and Atexcac. The geochemical analyses of water solutions showed that they were supersaturated to varying extents with several mineral phases, including aragonite, calcite, hydromagnesite, as well as hydrated Mg-silicates. Consistently, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analyses revealed that microbialites are composed of a diversity of mineral phases including aragonite and sometimes calcite, hydromagnesite, and more interestingly, a poorly-crystalline hydrated silicate phase. Coupling of scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry microanalyses on polished sections showed that this latter phase is abundant, authigenic, magnesium-rich and sometimes associated with iron and manganese. This mineral phase is similar to kerolite, a hydrated poorly crystalline talc-like phase (Mg3Si4O10(OH)2·nH2O). Diverse microfossils were permineralized by this silicate phase. Some of them were imaged in 3D by FIB-tomography showing that their morphology was exquisitely preserved down to the few nm-scale. The structural and chemical features of these fossils were further studied using a combination of transmission electron microscopy and scanning transmission X-ray microscopy (STXM) at the carbon and magnesium K-edges and iron L2,3-edges. These results showed that organic carbon is pervasively associated with kerolite. Overall, it is suggested that the poorly-crystalline hydrated magnesium-rich silicate forms in many alkaline lakes and has a strong potential for fossilization of microbes and organic matter. Moreover, the frequent occurrence of such an authigenic silicate phase in modern lacustrine microbialites calls for a reappraisal of its potential presence in ancient rocks.